Catheter ablation of persistent atrial fibrillation solely guided by complex fractionated atrial electrograms in a patient with persistent left superior vena cava - Iriki, Yasuhisa; Ishida, Sanemasa; Oketani, Naoya; Okui, Hideki; Ichiki, Hitoshi; Ninomiya, Yuichi; Kataoka, Tetsuro; Hamasaki, Shuichi; Tei, Chuwa (Journal of cardiology cases, 2010)
Catheter ablation in patients with persistent atrial fibrillation (AF) is challenging. There are few reports of catheter ablation for persistent AF with persistent left superior vena cava (PLSVC). We report an ablation case of persistent AF with PLSVC solely guided by complex fractionated atrial electrogram (CFAE). The subject was a 65-year-old man. Electroanatomic mapping system was used to integrate computed tomography data with 3D mapping data. We identified the CFAE sites on the electroanatomic mapping. Radiofrequency ablation was applied to the CFAE sites; the posterior aspect of left superior pulmonary vein (LSPV), the anterior ridge of left atrial appendage, and the roof at the anterior to the LSPV. After those ablations, AF was finally terminated by ablation in the middle of the PLSVC. Previous investigators have reported that pulmonary vein antrum isolation (PVAI) is effective for the management of patients with either paroxysmal or persistent AF. However, some patients experience episodes of AF despite successful PVAI, which implies that important triggers and perpetuators remain in the posterior left atrium, crista terminalis, superior vena cava, coronary sinus ostium, interatrial septum, and the ligament of Marshall/PLSVC. In conclusion, CFAE ablation was useful in a patient with persistent AF with PLSVC.